2021
DOI: 10.1182/blood.2020006921
|View full text |Cite
|
Sign up to set email alerts
|

CLEC12A and CD33 coexpression as a preferential target for pediatric AML combinatorial immunotherapy

Abstract: Emerging immunotherapies such as chimeric antigen receptor T cells have advanced the treatment of acute lymphoblastic leukemia. In contrast, long-term control of acute myeloid leukemia (AML) cannot be achieved by single lineage-specific targeting while sparing benign hematopoiesis. In addition, heterogeneity of AML warrants combinatorial targeting and several suitable immunotargets (HAVCR2/CD33 or HAVCR2/CLEC12A) were identified in adult AML. However, clinical and biologic characteristics differ between childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 49 publications
2
57
0
Order By: Relevance
“…approached 95% (14,28,29). A recent analysis documented the high level of expression of CLEC12A and CD33 on patient AML cells as compared to normal cells and noted that these two antigens together are expressed by nearly all pediatric AML (38). Therefore, targeting both CLEC12A and CD33 should be broadly effective in most AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…approached 95% (14,28,29). A recent analysis documented the high level of expression of CLEC12A and CD33 on patient AML cells as compared to normal cells and noted that these two antigens together are expressed by nearly all pediatric AML (38). Therefore, targeting both CLEC12A and CD33 should be broadly effective in most AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional AML targets that have been investigated for CAR therapies include CD33 [ 35 ], CLEC12A [ 36 ], the high-affinity folate receptor beta [ 37 ], and B7-H3 [ 38 ]. Beyond adoptive cell therapeutic strategies, bi- and tri-specific killer engager (BiKE and TriKE, respectively) approaches appear promising as AML treatment [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…CLEC12A, also known as C-type lectin-like molecule-1 (CLL-1), is a myeloid differentiation antigen expressed by 90–95% of leukemic blasts [ 69 , 70 ]. Additional support for using CLEC12A as an immunotherapy target comes from a recent expression study in pediatric AML patients that showed that the combination of CD33 and CLEC12A was the most frequently upregulated one in pediatric AML samples, making it a potential therapeutic target with limited on-target off-leukemia side effects [ 71 ]. CLEC12A has been evaluated as an immunotherapy target both with antibody-drug conjugates (ADCs) and bispecific antibodies.…”
Section: Antigen Targetsmentioning
confidence: 99%